2012
DOI: 10.1149/2.011211jes
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Intercalation of Bis(trifluoromethanesulfonyl)imide Anions from an Ionic Liquid Electrolyte into Graphite for High Performance Dual-Ion Cells

Abstract: Dual-graphite cells have been proposed as electrochemical energy storage systems using graphite as both, the anode and cathode, whereas the electrolyte cations intercalate into the negative electrode and the electrolyte anions intercalate into the positive electrode during charge. On discharge, cations and anions are released back into the electrolyte. In this contribution, we present highly promising results for "dual-ion cells" based on intercalation of bis(trifluoromethanesulfonyl)imide anions into a graphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
353
1
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 307 publications
(370 citation statements)
references
References 78 publications
7
353
1
9
Order By: Relevance
“…and the operation conditions (i.e. upper cut-off potential, operation temperature) (3,8). So far, we found a maximum specific discharge capacity of 115 mAh g -1 for the intercalation of TFSI -((CF 3 SO 2 ) 2 N -) anions into graphite at a temperature of 60 °C (11), whereas the intercalation capacity for lithium into graphitic carbon is usually very close to the theoretical value of 372 mAh g -1 (14).…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…and the operation conditions (i.e. upper cut-off potential, operation temperature) (3,8). So far, we found a maximum specific discharge capacity of 115 mAh g -1 for the intercalation of TFSI -((CF 3 SO 2 ) 2 N -) anions into graphite at a temperature of 60 °C (11), whereas the intercalation capacity for lithium into graphitic carbon is usually very close to the theoretical value of 372 mAh g -1 (14).…”
Section: Introductionsupporting
confidence: 56%
“…By intercalation of cations, like lithium ions, donortype graphite intercalation compounds (GICs) are formed, while the intercalation of anions yields acceptor-type GICs (3).…”
Section: Introductionmentioning
confidence: 99%
“…LICs, are a special form of "hybrid capacitors," i.e., a combination of a supercapacitor electrode and a battery electrode in one device, i.e., both storage mechanisms (Li ion insertion/extraction and adsorption/desorption) occur simultaneously during charge/discharge ( Figure 15b). As like in dual ion batteries, which are based on a similar working mechanism [150][151][152][153], not only the electrode capacities but also the number of anions and cations in the electrolyte, thus the amount of electrolyte is decisive for the available energy density. Amatucci et al [154,155] reported in 2001 the use of nanostructured lithium titanate (LTO) as negative electrode in combination with an activated carbon positive electrode.…”
Section: Pre-lithiation In Lithium-ion Capacitorsmentioning
confidence: 99%
“…However, situation is changing as people begin to be aware of their outstanding merits as follows. First, many anions can intercalate into graphite reversibly [2][3][4][5][6], even though their sizes are much larger than Li + ; Second, a relatively high specific capacity of more than 110 mAh g À1 can be delivered [4,7,8]; Third, the potential for the intercalation process ranges from 4.5 to 5.5 V vs. Li/Li + , which is still a heavy task for most lithium-storage positive electrode materials at present [9][10][11]. Apart from the above, the beneficial properties also include low cost, high electronic conductivity, abundant sources et al In short, anion-intercalated graphite compounds are qualified to pave a way for some new types of electric storage devices.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, much attention has been focused on ionic liquids which allow reliable operation in highly oxidizing circumstance [1,2,5,[8][9][10][12][13][14][15][16]. However, the drawbacks such as relatively poor compatibility with graphitic electrodes and high viscosity at room temperature may become problems in practical applications [10].…”
Section: Introductionmentioning
confidence: 99%